The Development of English Learning Video to Enhance Students’ Reading Comprehension Skill - Rahmanisa; Niah, Siti; Pahmi, Pahmi (Universitas Lancang Kuning, 2024)
Developing innovative learning media is needed at school nowadays, with learning media the learning goal will be easier to achieve. The aim of this research is to prove whether there is an enhancement in students’ scores in reading comprehension test after being treated by using learning video in learning process. This research is Research and Development using the model of ADDIE and data analysis of the products using likert scale. Data collection methods using questionnaires and test. Data processing was completed by using SPSS. The study participants were IPS students in the 10th grade from SMAN 2 Pekanbaru. The enhancement testing was done on students to calculate the rise in student scores after using learning video. The results of the validity of learning videos from media expert is 96% which categorized “very good”, the scores form material expert is 92,5% which also categorized “very good”. To ascertain the enhance in students' reading comprehension skill, the statistical analysis tests were carried out namely the mean and paired sample t-test. The significance value is 0.00, which means it fewer than 0.05, it might be ascertained that there is a significant influence among the results of the students' pre-test and post-test. The result shows that any enhancement of using learning video toward students’ reading comprehension skill.